Archaeodiacyclops, new genus with “archaic” features (Crustacea, Copepoda, Cyclopoida), with description of new species from water bodies of northern Sakhalin Island - Alekseev, Victor; Chaban, Olga (Zootaxa, 2024)
Representatives of freshwater cyclopid Archaeodiacyclops okhensis gen. nov., sp. nov. were found in river ecosystems of northern Sakhalin Island (East Russia). General structure of these specimens corresponds to genus Diacyclops. An unusual feature of these specimens is the retained hairs on the inner side of the caudal branches, which are usually absent in the genus Diacyclops. Analysis of the world fauna of the genus Diacyclops made it possible to describe a new genus and include the newly described species there, along with five already known species. The main diagnostic features for the new genus, in addition to the structure of the fifth pair characteristic of Diacyclops, are the combination of the unreduced structure of antennules (17-segmented), swimming legs (3-segmented) and caudal rami with presence of hair-setules on the inner side. The new genus includes 5 species, distributed mainly in the water bodies of the Americas. The finding of the newly described species outside this region is an additional evidence of some similarity of American and East Asian freshwater faunas. The article provides an identification key for species of a new genus.